The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1063/1.3153945
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of ion nitrided stainless steel

Abstract: The magnetic properties and crystalline structure of expanded austenite obtained by ion beam nitriding of AISI 316 steel are investigated. Magnetic force microscopy reveals that the nitrogen expanded austenite has two different layers, an outermost ferromagnetic layer and a paramagnetic layer beneath it. Superimposing the nitrogen concentration profile determined by secondary neutral mass spectrometry and the magnetic force microscopy image, one can see that the paramagnetic-ferromagnetic transition takes plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 45 publications
(38 reference statements)
0
24
0
1
Order By: Relevance
“…Larger domain size and different domain morphology observed for the 6 and 20 h samples may be due to thicker γ N layers and due to the distribution of CrN particles within the γ N matrix. A recent investigation [25] of magnetic and structural properties of an ion nitrided 316 SS suggest that magnetic domain pattern variations can be associated with crystal anisotropy, grain boundary, crystalline Table 2 Lattice parameters, a, in Å for the CoCrMo alloy fcc γ substrate phase and the fcc γ N phase. Δa/a refers to the relative difference in lattice spacing and is given by Δa/a = [{a(γ N ) − a(γ)} / a(γ)].…”
Section: Magnetic Behaviormentioning
confidence: 99%
“…Larger domain size and different domain morphology observed for the 6 and 20 h samples may be due to thicker γ N layers and due to the distribution of CrN particles within the γ N matrix. A recent investigation [25] of magnetic and structural properties of an ion nitrided 316 SS suggest that magnetic domain pattern variations can be associated with crystal anisotropy, grain boundary, crystalline Table 2 Lattice parameters, a, in Å for the CoCrMo alloy fcc γ substrate phase and the fcc γ N phase. Δa/a refers to the relative difference in lattice spacing and is given by Δa/a = [{a(γ N ) − a(γ)} / a(γ)].…”
Section: Magnetic Behaviormentioning
confidence: 99%
“…Similar MFM analyses of nitride austenitic stainless steel samples were reported in Refs. [74,83] .MFM imaging on polished cross-sections of nitrided steel samples revealed that such sub-grain magnetic domains appeared only in the outer part of a nitride layer, i.e. where the nitrogen supersaturation is higher than the inner part as confirmed by SEM-EDX linear scans.…”
Section: Structural Characterizations By Atomic (Magnetic) Force Micrmentioning
confidence: 88%
“…The paramagnetic to ferromagnetic transition occurs by two mechanisms, namely, the rearrangement of 3d electrons after changing FeCrNi atomic distances and the formation of metallic nitrides [36]. In the nitride FeCrNi stainless steel, the induced ferromagnetism implies the dominant Cr-N interaction which removes the Cr 3d electrons from the metal alloy valence band and leaves ferromagnetic Fe and Ni [83] . Moreover, the magnetic domains observed suggest heterogeneous distribution of the Cr-N bonds inside the nitrided austenite.…”
Section: Structural Characterizations By Atomic (Magnetic) Force Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…Low temperature nitriding produces thin layer of expanded austenite phase which improve their hardness and corrosion resistant. This expanded austenite phase is ferromagnetic [5,6]. Furthermore this phase cause weakly ferromagnetic properties of nitride austenitic stainless steel.…”
mentioning
confidence: 99%